A Comparative Study of Tranexamic Acid and Ethamsylate in Dysfunctional Uterine Bleeding - Deeksha, T; Kumar, M Ashok; Suresh, Gouri (Journal of Pharmacy Practice and Community Medicine)
Background: Dysfunctional Uterine Bleeding is irregular uterine bleeding that occurs in the absence of recognizable pelvic pathology, general medical disease or pregnancy. Bleeding may be excessively heavy or light and may be prolonged, frequent or random. About 1-2% of women with improperly managed an ovulatory bleeding eventually may develop endometrium cancer. There is less evidence which states the effectiveness of both the drugs because of which this study has been performed. Aim and Objectives: The objective of the study was to compare the efficacy of tranexamic acid and ethamsylate and to study the reduction in heavy menstrual bleeding. Materials and Methods: This study is a prospective comparative study which was conducted at Employee State Insurance Hospital, Ayanavaram, and Chennai. Of 56 patients recruited for the study with randomisation, 28 patients were in group A (tranexamic acid) and 28 patients were in group B (ethamsylate). Four patients were lost for follow up and two patients discontinued the given drugs. Hence 50 patients were included in the study. Group A received Tranexamic acid 500mg, BD, from 1 to 5 days of the menstruation for three consecutive cycles. Similarly Group B received Ethamsylate 500mg, BD from 1 to 5 days of the menstruation for three consecutive cycles. Results: Female patients between the age group of 39-45 years are mostly affected with dysfunctional uterine bleeding (DUB). PBAC mean score showed a significant reduction in menstrual blood loss both with tranexamic acid (293.84± 137.50) and ethamsylate (326.24±83.89), but tranexamic acid proved to be more efficacious. Hb level in tranexamic acid (12.96± 0.99) group was seen to be increased slightly when compared with ethamsylate group (12.024±1.07). The Endometrium thickness of the patients receiving tranexamic acid (3.404± 0.99) was between the normal ranges. Use of tranexamic acid and ethamsylate improved health-related quality of life. Conclusion: This study suggests that both tranexamic acid and ethamsylate are effective in management of dysfunctional uterine bleeding. Tranexamic acid was superior to ethamsylate in terms of effectiveness, reduction in blood loss and improvement in quality of life.
Keywords: Dysfunctional uterine bleeding; Endometrium thickness; Tranexamic acid; Ethamsylate; Menstruation.